1993
DOI: 10.1073/pnas.90.8.3452
|View full text |Cite
|
Sign up to set email alerts
|

Two members of a distinct subfamily of 5-hydroxytryptamine receptors differentially expressed in rat brain.

Abstract: We report two serotonin (5-hydroxytryptamine, 5-HT) receptors, MR22 and REC17, that belong to the G-protein-associated receptor superfamily. MR22 and REC17 are 371 and 357 amino acids long, respectively, as deduced from nucleotide sequence and share 68% mutual amino acid identity and 30-35% identity with known catecholamine and 5-HT receptors. Saturable binding of 125I-labeled (+)-lysergic acid diethylamide to transiently expressed MR22 in COS-M6 cells was inhibited by ergotamine > methiothepin > 5-carboxami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
2

Year Published

1994
1994
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(79 citation statements)
references
References 33 publications
2
75
2
Order By: Relevance
“…However, ketanserin is not an (Amlaiky et al, 1992;Adham et al, 1993;Lovenberg et al, 1993b), 5-HT5 (Erlander et al, 1993;Matthes et al, 1993), 5-HT6 (Monsma et al, 1993) and 5-HT7 (Lovenberg et al, 1993a;To et al, 1995). mRNA for the 5-HTIF, 5-HT5B and 5-HT7 receptors have been detected in the raphe nuclei (Bruinvels et al, 1994;Wisden et al, 1993;Erlander et al, 1993;To et al, 1995), suggesting that they have autoreceptor function. In the guinea-pig whole cortex the slopes of the agonist curves for 5-HT and 5-CT were shallow, which may also indicate the existence of multiple autoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…However, ketanserin is not an (Amlaiky et al, 1992;Adham et al, 1993;Lovenberg et al, 1993b), 5-HT5 (Erlander et al, 1993;Matthes et al, 1993), 5-HT6 (Monsma et al, 1993) and 5-HT7 (Lovenberg et al, 1993a;To et al, 1995). mRNA for the 5-HTIF, 5-HT5B and 5-HT7 receptors have been detected in the raphe nuclei (Bruinvels et al, 1994;Wisden et al, 1993;Erlander et al, 1993;To et al, 1995), suggesting that they have autoreceptor function. In the guinea-pig whole cortex the slopes of the agonist curves for 5-HT and 5-CT were shallow, which may also indicate the existence of multiple autoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…Although the functional significance remains to be revealed, the interest in these receptor subtypes have increased after the demonstration that several antipsychotic drugs including clozapine, chloropramazine, risperidone and olanzapine display a significant affinity for these sites [24]. Two subtypes of the 5-HT 5 receptor (5-HT 5A and 5-HT 5B ), sharing 70% overall sequence identity, have been found in rodents, whereas only the 5-HT 5A subtype has been found in humans [25,26]. Recent studies have shown that the human recombinant 5-HT 5A receptor activation produced an inhibition of cAMP production, indicating negative coupling to cAMP via Gi and Go [27]; however, the receptor may also couple positively to cAMP.…”
Section: -Ht Receptorsmentioning
confidence: 99%
“…5-CT has nanomolar affinity for 5-HT 7 receptors [33,85], it also binds to 5-HT 1A , 5-HT 1B and 5-HT 1D receptors although with lower affinities [32,72,171]. In addition, 5-CT also expresses affinity for 5-HT 5 receptors [57] whereas it is less potent at 5-HT 4 receptors [38]. Boess and Martin [33] have reported that the affinity of 5-CT for 5-HT 4 receptors is approximatively 200-fold lower than for 5-HT 7 receptors.…”
Section: Effect Of Agonistmentioning
confidence: 99%